Najib Mahfudz's World View On Islamic Spirituality and Politics : Genetic Structuralism Analysis - Ahmad Subiyadi (Jurnal Hikmatuna, 2019)
ABSTRACT This research is a qualitative study by conducting a literature study, method of data collection in this study through two ways; determine the research object and restrictions on research problems that focus on an overview of community and political climate when the process of writing a novel Layali Alfu Lailah with Structuralisme Genetic. The result of this study indicates that the world view of Najib Mahfudz, about spirituality and political ethics are difficult to separated, because both are something inherent.Through this novel, Najib Mahfudz criticized religious in islam who are apathetic to politics, therefore the religious values held by several people, such as middle-class society. contribution of this study this novel Najib Mahfudz alsoexpressed his views to criticize the attitude of subduing themselves to reason in excess and subservience to authority and property, regardless of religious values and humanitarian ethics, as well as an overview of the social classes in Egypt. The issue of spirituality in literature of Najib Mahfudz could be seen from the lack of disagreement of Egyptians who do not carry out God's commands. Although they run, but they are more concerned festive ritual, without understanding the substance. The political ethics of Najib Mahfudz also criticized the attitude of intellectuals, scholars, and scholars, who are too preoccupied with his world so they did not have the social and political role, therefore he promote the concept of democracy socialism which gives freedom of thought and Najib Mahfudz agree with secularism system by rejecting theocracy (Islam) because it cause chaos and misery to people of Egypt.